2017
DOI: 10.24248/eahrj.v1i2.559
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic and Other Characteristics Associated With Behavioural Risk Factors of HIV Infection Among Male Mountain-Climbing Porters in Kilimanjaro Region, Tanzania

Abstract: Background: Alcohol consumption, marijuana use, unprotected sex, and multiple concurrent sexual partnerships are prevalent among youth globally. These factors are regarded as important behavioural risk factors for HIV infection. The aim of this study was to assess the sociodemographic and other characteristics associated with behavioural risk factors of HIV infection among male mountain-climbing porters working on Mount Kilimanjaro in Tanzania.Methods: This cross-sectional study enrolled a representative sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The above from the average amount of income may predispose MCPs vulnerable to behavioral risk factors for HIV infection [12]. A descriptive cross-sectional study among MCPs showed behavioral risk factors for HIV infection, including unprotected sex, multiple concurrent sexual partnerships, and substance use, including excessive alcohol consumption, and marijuana use, suggesting a need to motivate sexually active MCPs to engage in HIV prevention interventions [13]. Further, one-third of MCPs have never tested for HIV, despite engaging in high-risk behaviors for HIV infection [11].…”
Section: Introductionmentioning
confidence: 99%
“…The above from the average amount of income may predispose MCPs vulnerable to behavioral risk factors for HIV infection [12]. A descriptive cross-sectional study among MCPs showed behavioral risk factors for HIV infection, including unprotected sex, multiple concurrent sexual partnerships, and substance use, including excessive alcohol consumption, and marijuana use, suggesting a need to motivate sexually active MCPs to engage in HIV prevention interventions [13]. Further, one-third of MCPs have never tested for HIV, despite engaging in high-risk behaviors for HIV infection [11].…”
Section: Introductionmentioning
confidence: 99%